2008
DOI: 10.1186/1472-6831-8-34
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of AZM therapy in patients with gingival overgrowth induced by Cyclosporine A: a systematic review

Abstract: Background: In daily clinical practice of a dental department it's common to find gingival overgrowth (GO) in periodontal patients under treatment with Cyclosporine A (CsA). The pathogenesis of GO and the mechanism of action of Azithromycin (AZM) are unclear. A systematic review was conducted in order to evaluate the efficacy of Azithromycin in patients with gingival overgrowth induced by assumption of Cyclosporine A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…A systematic review done in 2008 on the efficacy of AZM on cyclosporine A-induced gingival enlargement revealed that a 5-day course of Azithromycin with Scaling and Root Planning reduces the degree of gingival overgrowth. 22 The present study revealed a similar result that azithromycin has a significant effect on the reduction of gingival enlargement on patients with cyclosporine A-induced gingival enlargement. It showed the pooled effect in terms of mean difference of 1.58(95%CI: 0.77-2.39).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…A systematic review done in 2008 on the efficacy of AZM on cyclosporine A-induced gingival enlargement revealed that a 5-day course of Azithromycin with Scaling and Root Planning reduces the degree of gingival overgrowth. 22 The present study revealed a similar result that azithromycin has a significant effect on the reduction of gingival enlargement on patients with cyclosporine A-induced gingival enlargement. It showed the pooled effect in terms of mean difference of 1.58(95%CI: 0.77-2.39).…”
Section: Discussionsupporting
confidence: 86%
“…The previous study didn't show the pooled effect of azithromycin on cyclosporine-induced gingival enlargement due to limited studies. 22 Meanwhile, Azithromycin has a statistically significant effect of reducing bleeding on probing tendencies in patients with cyclosporine-induced gingival enlargement with a mean difference of 1.32(95% CI: 0.39-2.24).…”
Section: Discussionmentioning
confidence: 99%
“…nifedipine) have been associated with gingival enlargement (7). The prevalence of this side‐effect varies from 5% to 50% in adults (79). For cyclosporine, the highest prevalence of gingival overgrowth was observed in children (191) and decreased with increasing patient age (152).…”
Section: Epidemiologymentioning
confidence: 99%
“…Wahlstrom et al 13 described two cases of gingival hyperplasia that improved after treatment with azithromycin. A systematic review revealed that a short course of azithromycin or metronidazole along with proper regular oral hygiene is helpful in reducing the degree of gingival overgrowth 14. There is a general agreement that an initial threshold serum concentration of the offending drug (phenytoin) is required to initiate gum hypertrophy and it has been suggested that the higher the serum concentration the quicker gum hypertrophy develops 15…”
Section: Discussionmentioning
confidence: 99%